TINDAK UJAR KOMISIF DALAM NOVEL THE STARS SHINE DOWN KARYA SIDNEY SHELDON (SUATU ANALISIS PRAGMATIK) - Amping, Syeren Theresya; Jansen, Frieda Th.; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
ABSTRACT This study entitled Commissive in the Novel The Stars Shine Down by Sidney Sheldon. In doing this research the writer used Austin’s theory (1962). Austin classifies the utterance according to the illocutionary meaning, those are verdictives, executives, commissives, behabitives, and expositives. Commissive act is a speech act that asks the speaker doing something in the future. This research is an attempt to identify, classify, and analyze the commissive in the novel The Stars Shine Down by Sidney Sheldon. The method that used in this research is the descriptive method. The data of commissive in the novel The Stars Shine Down were collected from novel. The data found in this research are identified and classified based on types of commissive, and analyzed the meaning of commissive in the novel The Stars Shine Down based on Austin’s theory. The result shows that the types and meanings found in the novel are promise (completing the tower, giving the building, and meeting with Marthin), engage (focus on, looking for smart people, giving a name, listening, seeing his sick father, building a hotel location, and buying a ticket), offering (read messages, lend money, and give advice), agree (Lara as an iron butterfly, Lara is bigger than her competitors, and beautiful city in Venice), intend (say something), guarantee (guard his father, complete the building, and Lara will success), mean to (go to New York), and declaration (assign new workers, send bert to London, and cancel the meeting). It is expected that the study can help the readers especially the students in learning pragmatics especially commissive in the novel The Stars Shine Down by Sidney Sheldon.Keywords: Commissive Act, Novel The Stars Shine Down, Pragmatic Analysis.